Analisis Penetapan Harga Jual Dengan Menggunakan Metode Cost Plus Pricing Untuk Pesanan Khusus Pada Luluk Bakery Kota Probolinggo - jamatun hasanah; Judi Suharsono; R Hery Koeshardjono (JUMAD : Journal Management, Accounting, & Digital Business, 2023)
The purpose of the study was to determine the results of determining the selling price of torn bread with special orders using the cost plus pricing method and not the calculation method. Adding the cost by a percentage calculated by the formula determines the selling price based on cost plus pricing. The type of research used is quantitative descriptive with field study data collection methods in the form of interview, conservation and dokumentation. The results showed that it the production process of 1.350 torn bread requires 225 kg of wheat flour, 56 kg of eggs, and requires direct labor of 4 employees, whilw factory overhead costs according to the company require costs of Rp 2,727,500, in contrast to the calculation of the cost plus pricing which is Rp 2,252,000. The selling price according to Luluk Bakery Kota Probolinggo is Rp 7,500/box while the calculation of the variable costing approach is higher than the company because it includes all element of cost so as to generate real profits